2005
DOI: 10.1001/archfaci.7.6.393
|View full text |Cite
|
Sign up to set email alerts
|

Use of BioGlue Surgical Adhesive for Brow Fixation in Endoscopic Browplasty

Abstract: Objective:To determine the efficacy, longevity, and safety of BioGlue Surgical Adhesive for periosteal fixation in endoscopic browlifts.Methods: Retrospective review of 80 patients who underwent endoscopic browlift using BioGlue as the primary means of periosteal fixation. Visits were categorized as preoperative, 1 to 2 months, 3 to 6 months, and 7 to 12 months, and photographs of the first 15 patients were evaluated for change in brow position at each of these visits. Brow position was measured at the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Preoperative and postoperative photographic analyses of brow position, such as those performed by Sidle et al 25 and Jones and Grover, 26 offer the most exact methods of aesthetic outcome measurements and should be incorporated into future studies in our efforts to scientifically objectify technique success and longevity. Likewise, accurate recording and reporting of complications aids in our understanding of technique safety and should be provided quantitatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative and postoperative photographic analyses of brow position, such as those performed by Sidle et al 25 and Jones and Grover, 26 offer the most exact methods of aesthetic outcome measurements and should be incorporated into future studies in our efforts to scientifically objectify technique success and longevity. Likewise, accurate recording and reporting of complications aids in our understanding of technique safety and should be provided quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Thirty-five patients underwent the endoscopic procedure and were followed for up to 18 months. Postoperative conscious frowning was reportedly reduced 20 to 100 percent, and subconscious frowning was reduced to 20 percent of preoperative levels.…”
Section: Endoscopic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, it was used in aortic surgery as well as in the treatment of bronchopulmonary fistulas. Later on, it was used in other types of surgery [15][16][17][18][19][20][21][22][23]. Although it has been reported that BioGlue is safe and effective with no or minimal adverse side effects, some reports indicate that BioGlue might cause an inflammatory response [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…It remains intact for up to 2 years and is then resorbed slowly and replaced by normal tissue [14]. Its use has been well established in other fields of surgery [15][16][17][18][19][20][21][22][23]. Because of the advantages of rapid polymerization, resistance, flexibility and the long durability we decided to use BioGlue as an adjunct to flap repair.…”
Section: Introductionmentioning
confidence: 99%